i -Winder: portable filament winding machine - M. R. M., Rejab; Ma, Quanjin; M. S., Idris; Mohamad Nazirul Mubin, Merzuki (2018)
Filament winding is a composite fabrication technique mainly used for open or close end structures. Filament winding offers the possibility of economically and reliably producing parts of complex shape. Filament winding is well suited to automation technique, which can produce products in many applications, such as pipe, pressure vessel. Filament winding machine is designed and used winding process, which can have different axes. Machine with more than four axes can be used for advanced application, six-axis winding machines usually have 3 linear and 3 rotation axes.